Examining the Difficulties in Identifying and Handling Cardiac Amyloidosis; Acquiring Important Knowledge and Robust Treatment Methods - Ali, Ghadir M. S.; Seme, William Ale Emmanuel; Dudhat, Kiran (Cardiovascular & Haematological Disorders - Drug Targets, 2024)
Systemic amyloidosis is a rare protein misfolding and deposition condition that causes slow organ failure. Each of the more than 15 exclusive sorts of systemic amyloidosis, which encourage amyloid production and tissue deposition, is introduced by a unique precursor protein. Amyloidosis can affect various organs, including the heart, kidneys, liver, nerves, gastrointestinal tract, lungs, muscles, skin, and soft tissues. It can either be acquired or hereditary. Insidious and doubtful signs often cause a put-off in diagnosis. In the closing decade, noteworthy progressions have been made in the identity, prediction, and handling of amyloidosis. Shotgun proteomics based on mass spectrometry has revolutionized amyloid typing and enabled the identification of novel amyloid forms. It is critical to correctly identify the precursor protein implicated in amyloidosis because the kind of protein influences the proper treatment strategy. Cardiac amyloidosis is a disorder characterized by the systemic accumulation of amyloid protein in the myocardium's extracellular space, which causes a variety of symptoms. The buildup of amyloid aggregates precipitates myocardial thickening and stiffening, culminating in diastolic dysfunction and, in due course, heart failure. We examine every kind of systemic amyloidosis in this text to offer practitioners beneficial equipment for diagnosing and treating those unusual diseases. This review presents a comprehensive analysis of cardiac amyloidosis and consolidates current methods for screening, diagnosis, evaluation, and treatment alternatives.
Keywords: systemic amyloidosis